(untitled) (Research, Society and Development, 2025)
Sporotrichosis is a fungal skin infection characterized by the formation of subcutaneous nodules with the development of ulcerative wounds. It is caused by fungi belonging to the Sporothrix schenckii group, normally found in soil. Sporotrichosis is considered a zoonosis because it can affect humans. Its main form of infection is through traumatic penetration of the fungus into the skin. The objective of this study is to report a clinical case of sporotrichosis in a spayed female feline treated at a veterinary hospital in the city of Ji Paraná, RO. The owner’s main complaint was the appearance of a deep ulcerated lesion on the animal’s right pelvic limb. No other changes were observed during treatment. Material was collected by means of an imprint of the lesion in order to perform cytological examination. Under the microscope, it was possible to observe a large amount of yeast-like fungal structures, compatible with the Sporothrix complex. The treatment consisted of itraconazole, administered orally, and a compounded ointment containing dexamethasone, copaiba oil and miconazole for topical use. The animal was returned every 30 days to observe the progress of the wound healing process; the treatment ended after a period of four months.